Interprofessional teaching in pharmacy : Promoting interprofessional collaboration during training-examples from the University of Marburg and the Fulda Clinic - Weber, Jennifer; Culmsee, Carsten; Radziwill, Roland (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2025)
Increasingly complex and patient-specific healthcare requires new approaches to the qualification of future specialists, with interprofessionalism and cooperation between the healthcare professions becoming more and more important. In order for the various professions to work well together in everyday working life, it is essential to learn this interprofessionalism during training. The subject of clinical pharmacy as "patient-oriented pharmacy" aims to optimize patient medication and drug therapy safety and thus to improve the health and quality of life of patients. In addition, by expanding the teaching content, the basis for interprofessional collaboration with physicians is already laid during the training. Teaching formats, such as exercises on case reports and prescription examples in small student groups or objective structured clinical examinations (OSCEs), can convey the interprofessional concept during the courses. At the Philipps University of Marburg, students from the faculties of medicine and pharmacy study together in interprofessional and interdisciplinary projects such as "Medicine meets Pharmacy." Here, both the medical perspective on patients and their illnesses and the pharmaceutical perspectives on drug therapy and drug risks with various side effects and interactions are considered. In addition, interprofessionalism can be further reinforced during the practical year by participating in interprofessional training wards (IPSTAs), as shown in an example at the clinic in Fulda.